Implementasi Pengelolahan Dermaga PT. Pelindo Multi Terminal Branch Belawan - Habib Fitrah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to determine the implementation of dock management at PT. Pelindo Multi Terminal Belawan where the dock must be managed well, so that output results are maximum. If each pier were managed by one operation, this is not the case currently, where two docks are managed by one operation, which results in negligence and lack of focus on one job, which results in many ships not reaching their loading and unloading targets as planned. Which is detrimental to the next ship that is queuing for the next loading and unloading. Further steps to achieve this goal include improving operational results, optimizing infrastructure and upgrading IT systems. Sub-Holding Purpose Multi Terminal offices can provide additional management by utilizing all office functions honestly, which will help workers maximize their work day and enjoy their position more. Employees perform better at work when they are happy and satisfied. will focus on just one area or just one pier for the office. This study uses a qualitative method.